2001
DOI: 10.1128/jvi.75.24.12241-12251.2001
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and RNA Replication of Tacaribe Virus Genome and Antigenome Analogs Require N and L Proteins: Z Protein Is an Inhibitor of These Processes

Abstract: Tacaribe virus (TV), the prototype of the New World group of arenaviruses, comprises a single phylogenetic lineage together with four South American pathogenic producers of hemorrhagic disease. The TV genome consists of two single-stranded RNA segments called S and L. A reconstituted transcription-replication system based on plasmid-supplied TV-like RNAs and TV proteins was established. Plasmid expression was driven by T7 RNA polymerase supplied by a recombinant vaccinia virus. Plasmids were constructed to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
163
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(183 citation statements)
references
References 29 publications
(35 reference statements)
17
163
0
3
Order By: Relevance
“…By using this system, we showed that Z is not required for RNA synthesis mediated by the LCMV polymerase (13), but, rather, Z exhibits a dose-dependent inhibitory effect on both LCMV transcription and RNA replication (7). Similar findings have been subsequently reported for the Z protein of Tacaribe virus (TV), a New World arenavirus (14).…”
Section: A Renaviruses Include Lassa Fever Virus (Lfv) and The Southsupporting
confidence: 75%
“…By using this system, we showed that Z is not required for RNA synthesis mediated by the LCMV polymerase (13), but, rather, Z exhibits a dose-dependent inhibitory effect on both LCMV transcription and RNA replication (7). Similar findings have been subsequently reported for the Z protein of Tacaribe virus (TV), a New World arenavirus (14).…”
Section: A Renaviruses Include Lassa Fever Virus (Lfv) and The Southsupporting
confidence: 75%
“…Arenavirus genomic replication requires L and an appropriate NP-encapsidated RNA template (27,28). Although NP is not essential for the catalytic activity of L itself ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LCMV is the prototype arenavirus; its genome includes two RNA segments, L and S, that use an ambisense strategy for gene expression. The L segment encodes the 90 amino acid Z protein, a zinc-finger protein implicated in budding (Pérez et al, 2003;Salvato et al, 1992), and the L protein, the RNA-dependent RNA polymerase, of 2210 amino acids (Fuller-Pace & Southern, 1989;Lee et al, 2000;Lopez et al, 2001;Singh et al, 1987). The S segment encodes the glycoprotein precursor (GP-C) and the nucleoprotein (NP) (Buchmeier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%